ANALISIS FAKTOR ATAS PENGAMBILAN KEPUTUSAN MAHASISWA UNTUK MEMILIH JURUSAN AKUNTANSI DI STIE PERBANAS SURABAYA - Erlita Risnawati (Universitas Hayam Wuruk Perbanas, 2012)
In any organization, decision making is considered very crucial. Decision making should be based on the information that is considered important as well. This research attempts to analyze the decision-making factors such as the image, interests, collective decision, and the availability of employment in the accounting department towards the decision for choosing STIE Perbanas Surabaya. This study is also expected to provide some information as the input for all parties who are interested in this crucial problem. The sample used was taken from the students of accounting department in STIE Perbanas Surabaya batch 2011. The questionnaires were distributed to them and then 435 copies of them were analyzed by means firstly factor analysis. Based on the analysis, it was found that the factors such as image factors, interests, collective decision, and the availability of employment decisions were proved to have effects on the accounting majors in STIE Perbanas Surabaya. It was also found new variables namely service and facilities.